Penerapan Data Mining Algoritma Fuzzy C-Means Dalam Pengambilan Keputusan Penyelenggaraan Kelas Kuliah Semester Reguler: Studi Kasus Program Studi Manajemen Institut Bisnis dan Informatika Indonesia 2012 - Akhmad Budi (Jurnal Informatika dan Bisnis, 2013)
Lecture management is a routine activity for higher education institution in every semester. Decisionmaking for determining proposed subject in every semester, predicting the number of participants andclasses will be better whether higher education institution uses historical data to find valuableknowledge for lecture planning in the future. Higher education institution can find appropriate patternin subjects selection for each cluster of student in every semester. In this research clustering techniqueis used with Fuzzy C-Means Algortihm in dividing group of students based on semester and GradePoint Average (GPA) for knowing subjects will be attended. Fuzzy C-Means Algorithm is usedbecause several subjects can have membership function in many clusters of student from differentsemester and GPA. Cluster that was formed from this research are 27 clusters.